Formulasi Krim Antioksidan Ekstrak Etanol Daun Ubi Jalar Ungu (Ipomoea batatas (L.) Lamk) Sebagai Anti Aging - Damaranie Dipahayu; Widji Soeratri; Mangestuti Agil (Universitas Indonesia, 2014)
Purple sweet potatoes leaves (Ipomoea batatas (L.) Lamk) Antin 3 variety (IBLA) are natural antioxidant sources because of its anthocyanins contents. IBLA was extracted with kinetic maseration method using 70% ethanolic solution. The aims of this research were determination of antioxidant activity of IBLA extract with DPPH (2,2-diphenyl-1-picrylhydrazil) scavenging activity assay and formulation of IBLA extract into cream with oil in water (o/w) base. Both the cream base and formulation were stored at 28oC for a period of 4 weeks to predict their stability. The evaluation parameters consisted of organoleptic, homogenity, pH value, viscosity, emulsion type, dispersive power, mechanic and freeze and thaw. Futhermore, the cream base and formulation were evaluated for their effects on skin moisture, curvature and pigmentation. The results showed that ethanolic extract of IBLA had antioxidant activity of 80.43 % compared to that of pure vitamin C. IC50 value of IBLA extract was 3.68 ppm while IC50 value of vitamin C was 2.96 ppm. The cream base and antioxidant cream had a physical stability for 4 weeks. The cream base and antioxidant cream had no effect on promoting skin moisture. The cream base had no effect in inhibiting curvature, but antioxidant cream was effective to inhibit curvature. The cream base showed no pigmentation inhibiting effect, but antioxidant cream was effective in inhibiting pigmentation.